Most of the girls are alright, but some aren't personality trajectory groups from ages 14 to 24 and some associations with outcomes . [article]. - Personality development
Personality traits show normative pattern s of development toward maturity during adolescence. Yet individuals follow these normative patterns to different degrees. This study used growth mixture modeling to charaterize personality development patterns and their association with outcomes in a population-based sample of 1,537 girls aged 14 to 24. The authors used latent class analysis to identify 3 trajectory groups labeled alright (47%), and trouble (11 %). Alright group members were more likely at the age of 24 to have completed college, remained involve with their families, and obtained a good jobs. Trouble group members were more like to be involved with drugs and alcohol, to display interpersonal problems and to behave antisocially. Growing up group members fell in between.